Balancing Trade and Sustainability: An Analysis of Sustainable Fisheries Management under the Indonesia-EFTA Comprehensive Economic Partnership Agreement - Intan Soeparna; Sheva Atha Nugroho; Roberto Reyes-Barrera (Universitas Negeri Semarang, 2025)
As trade in fish between Indonesia and the European Free Trade Association (EFTA) States intensifies under the Indonesia-EFTA Comprehensive Economic Partnership Agreement (IE-CEPA), it becomes paramount to harmonize international trade with sustainable fisheries management. This study delves into this crucial nexus, employing descriptive and analytical legal research methodologies. It scrutinizes the sustainable development provisions embedded within the IE-CEPA, examining how these trade regulations align with and support sustainable fisheries management principles. The study further investigates the compliance of Indonesia with these rules, focusing on the protection of marine fishery resources, the suppression of Illegal, Unreported, and Unregulated (IUU) fishing, and the promotion of sustainable fishing practices that safeguard fish stocks and marine ecosystems. Ultimately, this research underscores the potential for a positive synergy between trade liberalization and environmental stewardship, ensuring the long-term viability of fishery resources while fostering economic growth for both Indonesia and EFTA States.